ARTIFICIAL INTELLIGENCE DAN SELF-REGULATED LEARNING: TELAAH EPISTEMOLOGIS PERSPEKTIF TEORI BARAT DAN FILSAFAT ISLAM - Fawwaz Adzansyah Islamy; Mugiarti Nur Fadlilah; Rr Setyawati (STKIP Persada Khatulistiwa Sintang, 2025)
The development of artificial intelligence in higher education has transformed the ways students access, process, and construct knowledge, thereby generating significant epistemic implications for self-regulated learning. This article aims to examine the relationship between AI and self-regulated learning from an epistemological perspective by integrating Western theories and Islamic philosophy. The study employs a systematic literature review of scholarly publications from 2021 to 2025 that address artificial intelligence, self-regulated learning, and epistemic cognition among university students. The findings indicate that, from a Western perspective, AI is conceptualized as a cognitive and metacognitive tool that supports planning, monitoring, and reflective learning through adaptive feedback and personalized learning experiences. However, uncritical use of AI may weaken students’ epistemic agency and foster cognitive dependency. From the perspective of Islamic philosophy, AI is positioned as a wasilah (means) that holds epistemic value when used ethically and guided by intention (niyyah), moral conduct (akhlaq), and moral responsibility. This article underscores that the epistemic value of AI is not inherent in the technology itself, but is determined by the quality of students’ self-regulated learning and their epistemic awareness as learning subjects.